In Search of Ethnic Entrepreneurship Opportunities in the City - A Comparative Policy Study - Hadewijch van Delft; Cees Gorter; Peter Nijkamp (Tinbergen Institute, 1999)
The rapidly rising inflow of foreign migrants confronts policy-makers with many socio-economic problems. The negative externalities of uncontrolled immigration are well known and often hard to cope with. In recent years we have seen many policy initiatives based on self-reliance principles for ethnic groups. Against this background ethnic entrepreneurship has become a popular strategy, as it stimulates and encourages migrants to look after themselves with a limited support of the government. Such a policy becomes an increasingly important endeavour in many large cities. Besides the conventional educational support and training programmes, such a strategy would need to implementpolicy strategies aiming at self-employment. An emphasis on ethnic entrepreneurship seeks to exploit the economic potential and opportunities instead of focusing on the problems minorities encounter when entering the labour market. In ethnic entrepreneurship, this potential can be utilised in a creative way, especially if well-organised projects and initiatives are set up.In this paper, various assistance programmes and urban policies in several European cities aiming at favouring ethnic entrepreneurship will be systematically compared with the aim to draw lessons for effective labour market policies. The methodological approach will employ a systematic information base concerning self-employment strategies in the cities under investigation. A newly developed comparative statistical method for categorical information, viz. rough set analysis, will be used in order to identify critical success factors. The results suggest that utilisation of socialnetworks is most helpful to enhance self-employment among ethnic minorities. Finally, the paper offers some lessons for the establishment of socio-cultural and ethnic networks, for strategies for improving training and education and for improvement of access to facilities and financial resources.
Keywords: 330; Entrepreneurship-Ansatz; Ethnische Gruppe; Niederlande